A visual analysis of the Kelantan shadow play puppets / Fiona Wong E Chiong - Fiona Wong , E Chiong (2021)
Wayang Kulit Kelantan, or Kelantan shadow play, is a traditional Malay folk theatre form in the northern part of peninsular Malaysia, and parts of southern Thailand. It performs the Hikayat Maharaja Wana, a localised version of the famous Indian epic, Ramayana. However, with the diminishing state of Wayang Kulit Kelantan performances in recent years, there is lesser demand and necessity for puppeteers and puppet-makers in Kelantan to produce puppets. There is a lack of scholarship and in-depth research particularly on the visual analysis of the Wayang Kulit Kelantan puppets. From the visual analysis of the puppets, it is evident that most puppets are designed to portray the characters in keeping with Indonesian-Malay aesthetics terms of their refinement or coarseness. These principles apply to the characters, as well as in the manner that they are portrayed in puppets. However, the puppets are designed in such a manner that certain refined characters appear coarse-looking, and vice versa. In most instances such figures are not gods or human beings. An outstanding example is Hanuman Kera Putih. The puppets tend to conform to a certain structure or ‘formula’ consisting of a head in side-profile; upper torso en face; lower torso and limbs in side-profile; with ornamentation including headdress, clothing, and accessories filled with intricate motifs and patterns; as well as a platform or vehicle. Certain puppets of the same classification, though appearing very similar, can still be distinguished from each other based on certain features of characterization. In addition, the puppets also reflect Indian, Thai or Javanese influences. The principal characters—Seri Rama, Siti Dewi, Maharaja Wana, and Hanuman Kera Putih—tend to draw parallels with their counterparts in Indian, Thai and Javanese cultural iconography and visual manifestations. The puppets are portrayed differently by the puppet-maker according to his individual style, preference, interpretation, and artistry, based on the details of the puppets passed down from their teachers. Instead of following a certain ‘standard template’ of design, changes are often made to the overall structure of the puppet’s figure to accommodate the physical attributes of the puppet-making materials during the crafting process. Over time, each dalang and puppet-maker has developed a personalized design style for his puppets based on his understanding of the character, different from those made by his predecessors or teachers, and peers. A visual comparison among the stylistic variations of the puppets has been made in this study. The puppet-maker produces his own desired motifs and patterns in his puppets’ design, which amalgamate on a single surface reflecting a strong sense of eclectic appeal. These motifs and patterns—deriving from nature and thus carry localised names, including their symbolisms—resemble those in local traditional material cultures in Kelantan, such as textiles, woodcarving, silverwork, and wau. The level of intricacy and detailing in the motifs reflect the puppet-maker’s skill and perfection. In conclusion, this study shows the significance of the visual aspects of the Wayang Kulit Kelantan puppets as a means of preserving a highly important example of Malaysian cultural heritage.